2015
DOI: 10.1179/1362171815y.0000000038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of process parameters effects on dissimilar friction stir welding of AA1100 and A441 AISI steel

Abstract: A prominent benefit of friction stir welding process is to join plates with dissimilar material. In this study, an attempt is made to find effects of tool offset, plunge depth, welding traverse speed and tool rotational speed on tensile strength, microhardness and material flow in dissimilar friction stir welding of AA1100 aluminium alloy and A441 AISI steel plates. Here, one factor at a time experimental design was utilised for conducting the experiments. Results indicated the strongest joint obtained at 1.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…The FSW tool, during travelling, forwards the plastic materials from front to rear side with forging force and combines them. 1 The side of weld where the sense of tangential velocity of the rotating tool is parallel to the sense of the tool traverse is termed as advancing side (AS), and if opposite, retreating side (RS). 2 Existing disturbances and heat in FSW are causing changes in the impurities’ distribution and the grain size surrounding and the joint centre.…”
Section: Introductionmentioning
confidence: 99%
“…The FSW tool, during travelling, forwards the plastic materials from front to rear side with forging force and combines them. 1 The side of weld where the sense of tangential velocity of the rotating tool is parallel to the sense of the tool traverse is termed as advancing side (AS), and if opposite, retreating side (RS). 2 Existing disturbances and heat in FSW are causing changes in the impurities’ distribution and the grain size surrounding and the joint centre.…”
Section: Introductionmentioning
confidence: 99%
“…The nugget zone of this welded specimen is found to be completely free from various defects, such as porosity, tunnel voids, excessive flash, kissing bond defects, defective tightness, onion skin microstructures, cracksimilar root flaws, etc. [31] to [33]. Fig.…”
Section: Confirming the Competence Of Established Modelmentioning
confidence: 98%
“…The applied force for material flow is highly affected by tool tilt angle (TTA), which is an angle with negative position from forward transverse direction [20,21]. After passing the tool from SZ, the axial force causes the extruded material to fill the weld seam [22]. Three-dimensional observation of the joint area has indicated that the cross section consists of 4 main regions [23], that are schematically shown in Figure 6 passing the tool from SZ, the axial force causes the extruded material to fill the weld seam [22].…”
Section: Materials Flowmentioning
confidence: 99%
“…After passing the tool from SZ, the axial force causes the extruded material to fill the weld seam [22]. Three-dimensional observation of the joint area has indicated that the cross section consists of 4 main regions [23], that are schematically shown in Figure 6 passing the tool from SZ, the axial force causes the extruded material to fill the weld seam [22]. Threedimensional observation of the joint area has indicated that the cross section consists of 4 main regions [23], that are schematically shown in Figure 6: [20].…”
Section: Materials Flowmentioning
confidence: 99%